The study of stability of the ferric oxide sols by zeta /ζ/ potential - Bayarmaa, D; Khureltogoo, Kh (Mongolian Journal of Chemistry, 2014)
In this study ferric oxide sols solutions were prepared in presence of different electrolyte and their zeta potentials were measured by simplified electrophoreses method with protective semi membrane filters. The stability of these sols solution was affected by particles size and electrolyte pH. DOI: http://doi.dx.org/10.5564/mjc.v15i0.329 Mongolian Journal of Chemistry 15 (41), 2014, p85-88